Expert systems in mental health: innovative approach for personalized treatment - Andrade-Arenas, Laberiano; Rubio-Paucar, Inoc; Celis, Domingo Hernández; Yactayo-Arias, Cesar (Institute of Advanced Engineering and Science, 2024)
Custom classification of mental illnesses has emerged as a challenge for mental health specialists, often minimized by patients' lack of awareness of symptoms and the importance of early intervention. Therefore, the purpose of this research is to provide a comprehensive understanding of personalized treatment, encompassing both pharmacological and non-pharmacological options, specifically tailored to mental disorders, considering factors such as the patient's age and gender, among other relevant characteristics. In this context, the Buchanan methodology has been chosen as the framework for structuring a web-based expert system. This approach covers everything from problem identification to system implementation and subsequent evaluation. The survey results, with a total of 50 responses, reveal that the category